PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM – SAHAM PERBANKAN DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL - Sari Yuniarti (University of Merdeka Malang, 2010)
When Investor making an investment, they willing to get an optimal return, but on the reality, investor faced by uncertainty called risk. By making diversification, investor can be done by forming combination of portfolio to reduce the rate of risk and optimizes the rate of expected return. This research aimed atanalyzing the form of optimal portfolio at the stocks of banking by using Single Index Model based onportfolio chosen theory which was increased first time by Markowitz (1952). Data used was secondary data consisting the data of banking stocks price which was in LQ-45 during 2009. By using single index model where the combination of optimal portfolio was consisted of return and risk level of banking stock individually, composition of each candidate forming optimal portfolio was stock of BRI Bank, BCA, and BNI.